Pelatihan Pembuatan Indikator Asam Basa dari Bahan Alam - Fanisa Fitriyani; Andhika Ardiansyah; Risa Nurazkiah; Fina Sabrina; Nova Melinda Kinaro; Novaliyosi Novaliyosi; Membran Seprian; Sonny Rohimat; Emilia Dwi Oktavia; Hendriyastuti Hendriyastuti; Endah Sugiarti (Institut Teknologi dan Bisnis Semarang, 2024)
Math and science is a field that is closely related to everyday life and is challenging yet interesting because it provides a deep understanding of science and mathematics. In reality, there are still many students who have no interest in this field because they consider mathematics and science to be difficult and uninteresting. Increasing students' interest in math and science can be achieved by conducting interactive hands-on activities through training in the production of acid-base indicators from natural materials. This hands-on training provides a more concrete learning experience and is relevant to everyday life because students use natural materials, known as green chemical indicators, that are easily found around them as a substitute for synthetic chemical indicators. This allows students to understand the concepts of acids and bases through direct application. This lab is expected to increase their understanding and interest in math and science. The use of natural indicators also supports the principle of environmentally friendly learning, which is in line with the concept of green chemistry, which minimizes the use of hazardous chemicals. Through this lab, students are expected to not only gain an understanding of concepts, but also develop scientific process skills such as observation, analysis, and problem solving. This hands-on activity is expected to spark students' curiosity and enthusiasm for MIPA science.